1996
DOI: 10.1046/j.1365-2133.1996.141876.x
|View full text |Cite
|
Sign up to set email alerts
|

Milia en plaque

Abstract: A 59-year-old woman presented with milia grouped in plaques, in the preauricular areas, bilaterally. Follicle-damaging dermatoses, tumours and external agents, can lead to this peculiar clinical pattern. We outline the clinical and histological features which allow accurate diagnosis of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Lesions may be indurated, and can be unilateral or bilateral. MEP is associated with pseudoxanthoma elasticum, 33 discoid lupus erythematosus, 41,42 lichen planus, 32 trauma, and renal transplantation 40,43 but also arises in healthy persons. Dogra et al 43 suggested that cyclosporine may predispose patients to MEP based on two cases, 40 and its known association with comedones, acne, and cysts.…”
Section: Milia En Plaquementioning
confidence: 99%
“…Lesions may be indurated, and can be unilateral or bilateral. MEP is associated with pseudoxanthoma elasticum, 33 discoid lupus erythematosus, 41,42 lichen planus, 32 trauma, and renal transplantation 40,43 but also arises in healthy persons. Dogra et al 43 suggested that cyclosporine may predispose patients to MEP based on two cases, 40 and its known association with comedones, acne, and cysts.…”
Section: Milia En Plaquementioning
confidence: 99%
“…21 Nodular elastosis of FavreRacouchot syndrome is differentiated by its topography and the presence of comedones and associated actinic damage. Comedo nevus is present at birth or appears at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…8 The condition is so similar to MEP that it has been suggested that it may represent the final stage of this form of lichen planus. 9 It has also been speculated that MEP may represent a rare variant of mycosis fungoides or follic- ular mucinosis; however, histopathological and immunohistochemical evaluation of reported cases has rendered these hypotheses unlikely. 3 Three cases of milia secondary to lupus erythematosus have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of secondary milia en plaque have been described in patients with lupus erythematosus, pseudoxanthoma elasticum, lichen planus follicularis tumidus and lichenoid eruption, contact dermatitis, folliculotropic mycosis fungoides with cysts and comedones, follicular mucinosis and in patients in use of cyclosporine following organ transplantation, although doubt remains with respect to this last group. 1,[8][9][10] Comedone nevus and FavreRacouchot disease must also be differentiated from MEP. Distinction between primary and secondary milia is based on the presence of a causal factor for milia, as shown by the patient's history, physical examination or histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation